ARIMA Modeling for Monthly West Texas Intermediate Crude Oil Price Forecasting - Eka, Hidayat Agus Sofian; Wiharja, Jason Marvel (Lembaga Penelitian dan Pengembangan Matematika dan Statistika Terapan Indonesia, PT Anugrah Teknologi Kecerdasan Buatan PT Anugrah Teknologi Kecerdasan Buatan, 2024)
Crude oil is a non-renewable natural resource. It is one of the world's most important natural resources since it has many utilities. One of the best parameters for crude oil price is West Texas Intermediate (WTI). It is the main oil benchmark for North America sourced from the United States. It is important to predict WTI price since the price of crude oil will impact the price of other commodities, which also will impact human life. In this work, the Autoregressive Integrated Moving Average (ARIMA) approach is used to predict WTI price for the next 12 months with the monthly data from April 1, 2019, to April 1, 2023, which was collected from investing.com. The results ARIMA (1,2,1) with the best model for forecasting WTI price with accuracy value from error measurements MSE is 38,129117536, MAPE is 6,8128441%, and RMSE is 6,174882619. This forecasting will be useful as a consideration for various stakeholders and the government.